Head position and expressed emotion of adolescents with schizophrenia and their caregivers compared to non-patient controls - Ramsauer, Brigitte; Lotzin, Annett; Parzer, Peter; Resch, Franz (Psychopathology, 2013)
Background: Family interactions with schizophrenia patients and caregivers rated as high expressed emotion (EE) are characterized by increased negative non-verbal behaviour. Head position is one important component of non-verbal behaviour and has not been examined in relation to EE before. The aim of this pilot study was to investigate the influence of caregivers' EE on the head position of adolescents with schizophrenia and their caregivers. Sampling and Methods: 15 adolescent schizophrenia patients and 17 non-patient adolescents were videotaped during a 10-min problem-solving task with their caregiver. The head position was coded by the Berner System of Non-Verbal Behaviour. The caregivers' EE level (high EE vs. low EE) was measured by the Five-Minute Speech Sample. Results: Adolescent patients and non-patients showed a higher frequency of averted head positions towards high EE caregivers compared to low EE caregivers (β = 47.85, t = 2.41, p = 0.023). They displayed longer mean times of averting towards high EE caregivers compared to low EE caregivers (β = -1.78, t = -2.51, p = 0.018). An indirect approach was shown more frequently by adolescent patients towards low EE compared to high EE caregivers (β = 39.99, t = 2.31, p = 0.028). In contrast, non-patient adolescents showed a more indirect approach towards high EE caregivers compared to low EE caregivers. Caregivers of schizophrenia patients had head positions with a straight ahead lowered approach for a longer time compared to caregivers of non-patients (β = -29.75, t = -2.51, p = 0.018). Within the patient and non-patient groups, low EE caregivers showed longer total times of positions with a straight ahead lowered approach than high EE caregivers. Conclusions: High EE communication may be characterized by a higher ratio of averting head position in adolescents, which is especially pronounced in adolescents with schizophrenia. Low EE communication seems to be better adjusted by a more indirect approach being shown by the adolescent and straight ahead lowered head positions by the caregiver, especially when the adolescent suffers from schizophrenia.
Published online: October 3, 2012
Gesehen am 14.12.2021